Sử dụng vi điều khiển PIC16F877A thiết kế mô hình robot điều khiển bằng tay - Nguyễn, Năng Hải (Trường Đại học Đà Lạt, 2012)
This paper introduces the result of test research concerning designing and building arobot controller by hand. The system consicts of both software and hardware. The hardware is designed with four main parts: the input switch, the relay control, the central controller, the control power of motor.